PENERAPAN PENDEKATAN DEEP LEARNING BERBANTUAN MEDIA INTERAKTIF PEAR DECK UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SMA PADA MATERI GELOMBANG - Usman Almah Ribi; Syahril Syahril; Mitri Irianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe students' cognitive learning outcomes and evaluate the effect of implementing a deep learning approach assisted by Pear Deck interactive media on high school students' cognitive learning outcomes in wave materials. This research was a quasi-experimental study using a non-equivalent control group design. The population consisted of all eleventh-grade MIPA students at SMAN 16 Pekanbaru during the even semester of the 2025/2026 academic year. Samples were selected using a lottery technique, resulting in class XI.1 as the experimental class (31 students) and class XI.2 as the control class (29 students). Data were collected through a posttest consisting of 15 multiple-choice questions measuring cognitive levels C1 to C5. Data analysis involved descriptive statistics and inferential statistics using the Independent Samples t-Test via SPSS 27. The descriptive analysis showed that the average posttest score of the experimental class was 84.29 (Good category), while the control class scored 77.82 (Good category). The inferential analysis yielded a significance value of 0.034, which is less than 0.05. Thus, the alternative hypothesis (Ha) was accepted, indicating a statistically significant difference in cognitive learning outcomes between the two classes. It can be concluded that the application of a deep learning approach assisted by Pear Deck interactive media has a positive and significant effect on improving high school students' cognitive learning outcomes in physics, particularly on wave materials.